Operative versus non-operative treatment of humeral shaft fractures: A systematic review. (August 2020) - Sargeant, Harry William; Farrow, Luke; Barker, Scott; Kumar, Kapil
Background: Humeral shaft fractures are common but debate still occurs as to whether these are best managed operatively or non-operatively. We sought to undertake a systematic review and meta-analysis of randomised and non-randomised studies to clarify the optimal treatment. Methods: We performed a search for all randomised and non-randomised comparative studies on humeral shaft fracture. We included only those with an operative and non-operative cohort in adult patients. We undertook a meta-analysis of the following outcome measures: nonunion, malunion, delayed union, iatrogenic nerve injury and infection. Non-operative management was with a functional brace. Results: Non-operative management resulted in a significantly higher nonunion rate of 17.6% compared to 6.3% with fixation. Operative management had a significantly higher iatrogenic nerve injury rate of 3.4% and infection rate of 3.7%. All nonunions within the included studies went on to union after plate fixation. There was no significant difference in delayed union or patient reported outcome measures. There was a significantly increased risk of malunion with non-operative treatment however this did not correlate with the outcome. Discussion: Our findings suggest that in the majority of cases, humeral shaft fractures can be managed with non-operative treatment, and any subsequent nonunion should be treated with plate fixation.